2007
DOI: 10.1152/ajpcell.00383.2006
|View full text |Cite
|
Sign up to set email alerts
|

Upregulation of Na+/Ca2+ exchanger contributes to the enhanced Ca2+ entry in pulmonary artery smooth muscle cells from patients with idiopathic pulmonary arterial hypertension

Abstract: ] cyt ) in pulmonary artery smooth muscle cells (PASMC) is a major trigger for pulmonary vasoconstriction (49) and an important stimulus for pulmonary vascular medial hypertrophy by stimulating PASMC proliferation (7,22). Removal of extracellular Ca 2ϩ or blockade of Ca 2ϩ influx significantly inhibits agonist-mediated pulmonary vasoconstriction (35) and markedly attenuates mitogen-mediated PASMC proliferation (24,52,60). These observations indicate that Ca 2ϩ entry through Ca 2ϩ channels and/or Ca 2ϩ transpor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
55
0

Year Published

2007
2007
2012
2012

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(59 citation statements)
references
References 63 publications
4
55
0
Order By: Relevance
“…Zhang et al [161] demonstrated an upregulation of NCX and enhanced Ca 2+ entry via NCX reverse mode in pulmonary artery SMC from patients with idiopathic arterial hypertension. These authors previously showed that cultured human pulmonary artery SMC express high levels of NCX and that enhanced NCX activity in its reverse mode produced an increase in cytoplasmic Ca 2+ and promoted proliferation [163].…”
Section: Other Changes Involving Various Ion Channelsmentioning
confidence: 99%
“…Zhang et al [161] demonstrated an upregulation of NCX and enhanced Ca 2+ entry via NCX reverse mode in pulmonary artery SMC from patients with idiopathic arterial hypertension. These authors previously showed that cultured human pulmonary artery SMC express high levels of NCX and that enhanced NCX activity in its reverse mode produced an increase in cytoplasmic Ca 2+ and promoted proliferation [163].…”
Section: Other Changes Involving Various Ion Channelsmentioning
confidence: 99%
“…However, treatment aimed at inhibiting both L-type calcium channels and the reverse-mode of the sodium-calcium exchanger in airway smooth muscle may prove effective at reversing the increased contractile tone associated with airway obstruction. Interestingly, inhibition of the sodium-calcium exchanger is currently touted as a potential clinical strategy for treating hypertensive conditions associated with increased calcium ion influx through the reverse-mode of the sodium-calcium exchanger [37,38,42,46,47]. It is apparent that further in vivo study is required in order to determine whether or not the sodium-calcium exchanger plays a role in obstructive airway disease.…”
Section: Store-refilling In Asm S Hirota and Lj Janssenmentioning
confidence: 99%
“…23 The effective reduction in 5-HT-elicited contraction by ten millimoles per liter Ni 2þ , extracellular Ca 2þ removal, KB-R7943, the combination of SKF-96365 and nifedipine, or verapamil, compared to the modest reduction in contraction due to nifedipine and diltiazem, suggest that voltage-independent Ca 2þ entry is predominantly responsible for 5-HT contraction before birth. 19,20,69,70 The pharmacological profiling we performed indicates that TRP channels, but not reverse-mode NCX activity, are critical to Ca 2þ -dependent 5-HT-elicited PA contraction in fetal sheep. 49,53 A prominent role for TRP channels was not surprising, since they contribute significantly to contraction and Ca 2þ signaling in vascular myocytes of other species.…”
mentioning
confidence: 94%
“…23 Long-term hypoxia also augments NSCC activity in PA smooth muscle cells of adult rat. 24,25 Reports also show that NCX 20 and transient receptor potential (TRP) channels, which encode for NSCCs, contribute to the development of PA hypertension in humans. [26][27][28][29][30][31] Long-term hypoxia also increases platelet-activated factorinduced Ca 2þ responses in pulmonary venous smooth muscle cells of fetal sheep, 32 which may be a consequence of increased platelet-activated factor receptor expression and resultant inositol 1,4,5-triphosphate generation.…”
Section: Introductionmentioning
confidence: 99%